2011
DOI: 10.3109/09537104.2011.576284
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12and EP3 antagonists promote the inhibitory effects of natural modulators of platelet aggregation that act via cAMP

Abstract: Several antiplatelet drugs that are used or in development as antithrombotic agents, such as antagonists of P2Y₁₂ and EP3 receptors, act as antagonists at G(i)-coupled receptors, thus preventing a reduction in intracellular cyclic adenosine monophosphate (cAMP) in platelets. Other antiplatelet agents, including vascular prostaglandins, inhibit platelet function by raising intracellular cAMP. Agents that act as antagonists at G(i)-coupled receptors might be expected to promote the inhibitory effects of agents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…For example, it has been demonstrated that activation of platelet P2Y 12 receptors by ADP causes inhibition of platelet adenylyl cyclase, which reduces the ability of PGI 2 acting through prostaglandin IP receptors to elevate cAMP, and thus reduces platelet aggregation. Hence, blockade of platelet P2Y 12 receptors increases the sensitivity of platelets to the antiaggregatory and antisecretory effects of PGI 2 (8,9). This interaction is readily understandable, as both P2Y 12 receptors and PGI 2 have actions on a common signaling pathway, cAMP.…”
mentioning
confidence: 93%
“…For example, it has been demonstrated that activation of platelet P2Y 12 receptors by ADP causes inhibition of platelet adenylyl cyclase, which reduces the ability of PGI 2 acting through prostaglandin IP receptors to elevate cAMP, and thus reduces platelet aggregation. Hence, blockade of platelet P2Y 12 receptors increases the sensitivity of platelets to the antiaggregatory and antisecretory effects of PGI 2 (8,9). This interaction is readily understandable, as both P2Y 12 receptors and PGI 2 have actions on a common signaling pathway, cAMP.…”
mentioning
confidence: 93%
“…First, Fox et al [27] demonstrated that PGE 1 potentiated the anti-platelet effects of both cangrelor and clopidogrel. In a subsequent study from the same laboratory [29], it was also shown that the anti-aggregatory effects of the P2Y 12 inhibitors cangrelor, ticagrelor and the active metabolite of prasugrel were likely to be mediated, at least in part, by a potentiation of physiological activators of adenylate cyclase (such as PGI 2 /PGE 1 ). Furthermore, Cattaneo and Lecchi [28] had demonstrated that a substantial component of the effect of cangrelor in inhibiting platelet aggregation was engendered by reversing ADP-induced inhibition of adenylate cyclase signaling.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, a number of investigators have previously provided evidence that prostacyclin (PGI 2 ) and prostaglandin E 1 (PGE 1 ), powerful activators of platelet adenylate cyclase, potentiate clopidogrel effect [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PGE 2 -mediated stimulation of EP3 decreased cAMP, consistent with its primary signaling in platelets being coupled to G i [73]. The selective EP3 antagonist DG-041 abolishes the pro-aggregatory effects of both sulprostone [58] and low concentrations of PGE 2 [56, 63, 74]. …”
Section: Introductionmentioning
confidence: 99%